2021
DOI: 10.1002/fsn3.1903
|View full text |Cite
|
Sign up to set email alerts
|

Degree of hydrolysis, functional and antioxidant properties of protein hydrolysates from Grass Turtle (Chinemys reevesii) as influenced by enzymatic hydrolysis conditions

Abstract: Grass turtle (Chinemys reevesii) is an aquatic animal species of the Geoemydidae family, which is found in many countries, particularly in Hong Kong, China, Taiwan, Japan, and Korea (Dai et al., 2012). At present, research studies are focused on the practical utilization of various aquatic animal species products and their by-products (Zou et al., 2017). Tortoises and turtles have long been used for foods and medicines in the East and Southeast Asia, while China is the largest consumer country in the world. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 43 publications
6
24
2
Order By: Relevance
“…These values were higher than those reported by Noman [22] in hydrolysates of sturgeon fish, but they were lower than the results found by Md. Serajul [15] in Chinese grass turtles. On the other hand, the IC50 value is described as the concentration of protein hydrolysates that can scavenge 50% of DPPH free radicals.…”
Section: Antioxidant Activities Of Fish Protein Hydrolysates 2131 Dpp...contrasting
confidence: 71%
“…These values were higher than those reported by Noman [22] in hydrolysates of sturgeon fish, but they were lower than the results found by Md. Serajul [15] in Chinese grass turtles. On the other hand, the IC50 value is described as the concentration of protein hydrolysates that can scavenge 50% of DPPH free radicals.…”
Section: Antioxidant Activities Of Fish Protein Hydrolysates 2131 Dpp...contrasting
confidence: 71%
“…From the SEM images, it could be observed that the protein in KDF had degraded into small fragments after enzyme hydrolysis, with this increasing with the reaction time, which led to a reduction in the particle size of KPH compared to KDF under the same SEM parameters (Mag = 90× and AV = 2.0 kV/Mag = 345× and AV = 2.0 kV). These findings are in accord with those of Islam et al , 17 who mentioned that protein was degraded into small fragments with particle-size reduction after treatment by enzymes and reported that the reduced particle size may be the reason for the high solubility of the protein hydrolysates.…”
Section: Resultssupporting
confidence: 92%
“…According to SEM images, the protein degraded into small fragments and looser structure with many folds after enzyme hydrolysis, resulting in smaller particles compared with untreated samples with the same SEM parameters. The results are similar to other studies that reported protein had degraded into small fragments, and particle size had been reduced after enzyme treatment (Islam et al 2021;Fathi et al 2022).…”
Section: Scanning Electron Microscopysupporting
confidence: 91%
“…All freeze-dried samples were coated with a gold layer (COXEM). The SEM images of the samples were examined at 1000× magni cation (Islam et al 2021).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%